Pengaruh Latihan Continuous Running Terhadap Tingkat Kebugaran (Aerobik) Pada Siswa Sepak Bola Usia 15-18 Tahun Di Akademi Training Centre Kota Salatiga - Arifuddin, Erwin, Isnaini Herawati, S. Fis, M.Sc (2016)
Background: Aerobic Fitness is the ability of the heart, lungs, and blood vessels in the use of oxygen and use it to become a force that can be used to daily activity. Aerobic fitness is one of physical components which is be basic of soccer player, Fitness aerobics has a very important role on the activity of the game of football, and this is in play, the player is required to have perfect physical condition to be able to always be a concentration in the play as well as persisting in long time, so it is important to be kept by every player to always be ready and consistent and stable on the pitch. Objective: To know the influence of Continous Running to the level of aerobic fitness of football student aged 15-18 years in Training Centre Academy Salatiga city. Methods: The research method used in this research is Quasi-experiment using pre and post-test with control group design of 30 respondent which are divided into 2 groups, namely treatment group and control group. Aerobic fitness is measured by using cooper test that is 2,4 Km running test before exercises and after respondent have done the continous running excercise as long as 6 week, data were analyzed by using the Willcoxon signed rank test to test the effect and to observe the differences between treatment group and control group to aerobic fitness level of football academy aged 15-18 year student using Mann Whitney test. Results: The researcher find the influence of Continous Running to aerobic fitness level of student aged 15-18 years after the Statistical test using Wilcoxon test showed a p-value of 0.001 in the treatment group and the control group getting the p-value of 0.238 and to know the difference of influence between treatment group and control group by using Mann Whitney test obtained p-value 0,000. Conclusion: There are the influence of Continous Running to aerobic fitness level of student aged 15-18 years.